Islam in Politics and Dakwah: a reflection from Bapak Mohammad Natsir (1908-1993) - Ahmad, Nadzrah; Amir, Ahmad Nabil (IIUM Press, International Islamic University Malaysia, 2018)
This paper discusses the historical struggle of Bapak Mohammad Natsir (1908-1993) in the fields of politics and dakwah in Indonesia. It analyzes his contributions in raising the spectre of Islamic politics and dakwah driven by his significant struggle in Masyumi (Muslims Consultative Council of Indonesia), and DDII (Islamic Missionary Chamber of Indonesia), as well as from his substantive writings on the political ideal and aspiration of dakwah in Islam. The qualitative methodology is employed in this research in which materials that are related to the Mohammad Natsir are analyzed. Findings reveal that considerable contribution of Mohammad Natsir to the Muslims can be reckoned especially in the area of Islamic propagation and political organization of Indonesia.